The Use of Intercultural Approach in SLA to Improve Student’s Communicative Competence in 8th Grade - Kulsum, Umi; Hartono, Rudi (English Education Journal, 2023)
Intercultural understanding plays a vital role in language education. Having a good cultural or intercultural awareness can help students create good relationships and successful communication. This study aimed at explaining the use of the intercultural approach in second language acquisition to improve the students’ communicative competence in eighth grade. This study used the qualitative approach with narrative study. The data were taken from classroom observation, teacher and students interviews, and document analysis. Data were analyzed using five steps according to Miles and Huberman (1992) and Merriam (1992), namely transcribing the data, coding the data, reducing the data, displaying the data, and drawing a conclusion. This study found that the use of an intercultural approach concerned on its three components, such as knowledge, attitude, and behavior. Those components are provided to the students in the special meeting, but they could also be included in the materials listed in the syllabus. There were four stages of intercultural approach, namely warm-up, communicative activities, product, and discussion. Classroom activities in using intercultural approach were brainstorming, pair or work group, presentation, discussion, and reflection. In addition, the procedures of intercultural approach were exploring local culture, exploring language learning materials, exploring the traditional media and arts through English, exploring IT through English, cultural informants, and face-to-face intercultural communication. The findings of this study are expected to provide additional information regarding the proper use of intercultural approach in second language acquisition to improve the students’ communicative competence in eighth grade.